Assessment of microalgae for sustainable processing of palm oil waste - Bin Mohamed Fadzil, F; Fazriz Sani Mohamed Fadzil (2013)
Industrial production of palm oil adversely affects the environment since it contains substantial harmful quantities of solids as well as viscous and oily liquid. Due to the high capital expenditure and operationally intensive nature of current treatments, phycoremediation, which employs microalgae species, provides an alternative and sustainable method of biological wastewater treatment. Six microalgae species, Stichoccocus bacillaris, Brachiomonas submarina pulsifera, Tetraselmis sp., Dunaliella salina, Euglena mutabilis, and Oscillatoria sp. were initially investigated, due to the range of biochemical and physical characteristics, and to analyse the potential of each strain, given their less well-characterised information on the growth in industrial effluent and under different light regimes. Among the selected species, novel chlorophyta S.bacillaris and cyanophyta Oscillatoria sp. were found to grow successfully in palm oil mill effluent under 16:8 and 8:16 light regimes. In comparison to the growth observed in the control medium, chlorophyta S.bacillaris exhibited a highly significant increase in cell numbers when it was cultivated in palm oil mill effluent: 89.95% (p-value = 0.0004) and 87.72% (p-value = 0.0009) under the 16:8 light and 8:16 light regimes respectively. Chlorophyll and protein contents were also found to be significantly higher when cultivated in palm oil mill effluent than grown in the control medium. In parallel to the cells growth in palm oil mill effluent, the novel species was also able to remediate the industrial wastewater as there was a simultaneous decrease in palm oil loads after 10 days of cultivation and treatment. It was indicated by a significant decrease in Chemical Oxygen Demand (COD) by S.bacillaris; by 85.31% (p-value = 0.000027) and 80.88% (p-value = 0.000023) under 16:8 light and 8:16 light regimes respectively. Further assessment revealed the significant reduction of total phosphate by 93.07% (p-value = 0.00015) under 16:8 light and 88.25% (p-value = 0.000039) under 8:16 light, and nitrate by 78.14% (p-value = 0.00037) under 16:8 light and 72.9% (p-value = 0.00056) under 8:16 light. Although the cultivated cyanophyta Oscillatoria sp. in palm oil mill effluent showed an increase in cell counts, chlorophyll, and protein content under both light regimes, assessments of these factors showed them to be non-significant when compared to their growth in the control medium. Despite these results, pollution loads in palm oil mill effluent were significantly reduced by both species. COD was decreased by 78.22% (p-value = 0.00001), and 82.9% (p-value = 0.0000015) under the 16:8 and 8:16 light regimes respectively, whereas total phosphate and nitrate were both demonstrably reduced by between 78.69% and 85.85% under both light regimes. Turbidity level was also demonstrated to have reduced significantly in palm oil mill effluent after the cultivation of S.bacillaris, by 44.04 % (p-value = 0.013), and 19.08% (p-value = 0.0047) under 16:8 and 8:16 light regimes respectively, after 10 days of treatment. Oscillatoria sp. was consistently efficient at reducing turbidity, by 34.69% (p-value = 0.00435) under 16:8 light and 36.64% (p-value = 0.00006) under 8:16 light. Besides the importance of applied photoperiods for the study of algal biomass growth, the findings established also provide an insight into phycoremediation, an environmentally desirable and sustainable solution for pollutant removal. The optimisation of this technology requires further biochemical assessments in order to determine possible technoeconomic advantages of phycoremediation and the key parameters dictating pollution load reduction.